Impact of intelligence leadership on organizational excellence: Mediating role of organizational culture - Malek Alharafsheh; Ahmad Albloush; Rami Hanandeh; Medhat Alsafadi; Ayed Ahmad Khwlldh (Problems and Perspectives in Management, 2022)
The absence of intelligence leadership may lead to a failure to motivate employees within universities, which leads to adverse effects on organizational excellence, primarily if the prevailing organizational culture does not support the processes of development and success. Thus, organizational culture is expected to play an essential role in enhancing the leadership’s ability to use its intelligence to achieve organizational excellence. Accordingly, the study aims to identify the mediating role of organizational culture in the impact of leadership intelligence on achieving organizational excellence in Jordanian universities. Qualitative data were collected and quantitatively analyzed. A questionnaire was designed using a leadership intelligence scale and distributed to a sample of 371 faculty members in 33 Jordanian universities. The sample size was chosen according to the statistical tables, and this sample is considered statistically acceptable. The data were processed using structural equations using SPSS and AMOS software. The study concluded that there is an effect of intelligence leadership on organizational excellence. It was also found that organizational culture mediates the relationship between intelligence leadership and organizational excellence. Therefore, the study recommends that the decision makers in Jordanian universities strengthen intelligence leadership, with the need to establish clear foundations in the selection of university leaders, ensuring intelligence leaders’ existence.